Neuroprotection by chotosan, a Kampo formula, against glutamate excitotoxicity involves the inhibition of GluN2B-, but not GluN2A-containing NMDA receptor-mediated responses in primary cultured cortical neurons - Sachie Sasaki-Hamada; Azusa Suzuki; Emi Sanai; Kinzo Matsumoto; Jun-Ichiro Oka (Elsevier, 2017)
Chotosan (CTS), a traditional herbal formula called Kampo medicine, was shown to be effective in the treatment of vascular dementia in a clinical study, and exerted protective effects against transient cerebral ischemia-induced cognitive impairment in mice. In the present study, we investigated the neuroprotective effects of CTS using primary cultured rat cortical neurons. CTS (250-1000 μg/mL) inhibited neuronal death induced by 100 μM glutamate. This glutamate-induced neuronal death was blocked by a GluN2B-, but not GluN2A-containing NMDA receptor antagonist. Therefore, the neuroprotective effects of CTS were related to an inhibition of GluN2B-containing NMDA receptor-mediated responses.